Role of biomarkers in monitoring antiblastic cardiotoxicity. (May 2016) - Novo, Giuseppina; Cadeddu, Christian; Sucato, Vincenzo; Pagliaro, Pasquale; Romano, Silvio; Tocchetti, Carlo G.; Zito, Concetta; Longobardo, Luca; Nodari, Savina; Penco, Maria
Abstract : Early detection of anticancer drug-induced cardiotoxicity (CTX) has been evaluated by most international scientific cardiology and oncology societies. High expectations have been placed on the use of specific biomarkers. In recent years, conventional biomarkers and molecules of more recent interest have been tested and compared in the context of anticancer drug-related CTX. Encouraging results were obtained from studies on molecules of myocardial damage, such as troponin and markers of myocardial wall stress, including circulating natriuretic peptides, as well as from the assessment of the products of inflammation or circulating levels of free radicals. However, clear guidelines on their sensitivity, specificity, and accuracy are not yet available, and many challenges, such as the optimal time of assessing, optimal schedule for evaluation, optimal cut-off point for positivity with the highest level of specificity, and optimal comparability of different assays for the measurements, remain unresolved. Given the importance of having a reliable and accurate tool for monitoring anticancer drug-induced CTX, this review will focus on the available data on the most effective and widely used biomarkers and the studies that are currently underway that aim to identify the effectiveness of new approaches in this therapeutic setting.